A taxonomic survey of Caridean and Penaeid shrimp in Lapinig Bay, Northern Samar. - Juarez, Bridgette M. (Bridgette M. Juarez, 2018)
There are no recent inventory on caridean and penaeid shrimp species in the Samar islands. Furthermore, no studies related to taxonomy of all caridean and penaeid shrimp have been conducted in Lapinig Bay, Northern Samar. Thus, this study is aimed to survey the marine, and brackish caridean, and penaeid shrimp present in the municipality. Caridean and penaeid shrimps were collected in the different areas of the bay with varying depth and salinity from January to March 2018.